Metode Pembentukan Karakter Religius Melalui Taman Pendidikan Al-Qur’an (TPQ) Miftahul Huda (Desa Segaralagu, Kecamatan Cipari, Kabupaten Cilacap) - Nita Indriyani; Sri Haryanto; Darul Muntaha (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to: 1) Identify the methods used by instructors in developing religious character through Qur’anic education at Taman Pendidikan Al-Qur’an (TPQ) Miftahul Huda, located in Segaralangu Village, Cipari District, Cilacap Regency; 2) Describe the implementation of religious character-building methods at the institution; and 3) Analyze the supporting and inhibiting factors in applying these methods. The research employs a descriptive qualitative approach with field research as its design. Data collection techniques include observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results indicate that the methods used for developing religious character include habituation, exemplary behavior, lectures/advice, as well as rewards and punishments. The learning process at TPQ involves habitual practices such as praying before and after lessons, disciplinary measures for tardy students, and promoting respectful behavior toward teachers and peers. Supporting factors include the presence of competent instructors, many of whom are alumni of TPQ Miftahul Huda, motivated students who actively participate in learning, adequate learning facilities, and a conducive learning environment. Inhibiting factors include unmotivated teachers, students with low learning motivation or who are prone to joking during lessons, lack of student preparedness (e.g., not bringing learning materials such as the Qur’an), and limited infrastructure, particularly classroom space, which necessitates a two-session system (day and afternoon classes).